Analisis Pengaruh Komposisi Oksida Abu Sekam Padi dan Serbuk Ban Terhadap Karakteristik Marshall Campuran Asphalt Concrete-Wearing Course (AC-WC) - Deby Ansyory; Hendrik Jimmyanto; Ramadhani Ramadhani; Desmarita Desmarita; Siti Anisah (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2026)
The utilization of waste materials as alternative components in pavement construction is continuously being developed to support sustainable development. This study examines the use of Rice Husk Ash (RHA) and Crumb Rubber (CR) as substitute materials in Hot Mix Asphalt (HMA) specifically for Asphalt Concrete-Wearing Course (AC-WC). The research investigates the chemical characteristics of these materials through X-Ray Fluorescence (XRF) testing and evaluates their impact on mixture performance based on Marshall parameters. The methodology involved material characterization, the design of Marshall samples with asphalt content variations ranging from 5% to 7%, and Marshall testing on both control samples and modified samples containing a 50% RHA and 50% CR filler substitution. XRF analysis revealed that RHA is predominantly composed of Silica (SiO2) at 91.5%, while CR contains 51% Zinc Oxide (ZnO) and 17% Sulfur (SO3). Marshall test results indicate that the high silica content in RHA contributes significantly to increasing mixture stability beyond 1400 kg, though it also leads to higher Voids in Mix (VIM). Conversely, the inclusion of CR enhances flexibility and flow values but reduces overall stability due to the elastic properties of sulfur and zinc oxide, which limit the internal bonding of the mixture. This study concludes that the mechanical characteristics of asphalt mixtures are heavily influenced by the chemical interactions of their constituent oxides, where RHA serves as a structural stiffener and CR acts as an elasticity modifier.